IDENTIFIKASI KESULITAN SISWA SMP DALAM MENGERJAKAN SOAL ARITMATIKA SOSIAL - Ati Rusmiati; Siti Chotimah (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
Social arithmetic is material that is directly related to the application of mathematics in everyday life. But the facts show that students find it difficult to learn the material. This study was conducted with the aim of describing the identification of the difficulties of junior high school students in working on social arithmetic problems. In this research using a qualitative descriptive method. The data taken using the technique of giving test questions in the form of descriptions to students with indicators that have been set as instruments consisting of 6 questions, then further analyzing student answers. Data analysis was carried out, namely data reduction, data presentation and conclusion drawing. The analysis aims to determine the students' difficulties in social arithmetic lessons. The object of research is 25 students in one of the Cililin State Junior High Schools. The instrument is a test question regarding social arithmetic with different levels of questions. The results showed that there were 3 types of difficulties, namely: (1) difficulties in language aspects, such as students having difficulty understanding and translating questions and even difficulty in retelling in their own language; (2) Difficulty in the prerequisite aspects, the sequence from the language aspect makes students unable to copy back what is known and what is asked, students also understand a little about the concept of determining formulas; (3) difficulties in applied aspects, for example, students have difficulty carrying out counting methods, making it difficult for students to determine the common thread from these answers. This difficulty is caused because students do not fully understand the social arithmetic material.